2014
DOI: 10.1302/2046-3758.36.2000239
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after total hip replacement surgery

Abstract: Total hip replacement causes a short-term increase in the risk of mortality. It is important to quantify this and to identify modifiable risk factors so that the risk of post-operative mortality can be minimised. We performed a systematic review and critical evaluation of the current literature on the topic. We identified 32 studies published over the last 10 years which provide either 30-day or 90-day mortality data. We estimate the pooled incidence of mortality during the first 30 and 90 days following hip r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 68 publications
6
114
1
Order By: Relevance
“…16,17 We found that in our cohort, the NSQIP-ACS risk calculator 18 had underestimated mortality considerably for patients with the demographics and comorbidities found in our sample. The calculator predicted average mortality of 12% for emergency and 7% for nonemergency hip fracture surgery.…”
Section: Discussionmentioning
confidence: 65%
“…16,17 We found that in our cohort, the NSQIP-ACS risk calculator 18 had underestimated mortality considerably for patients with the demographics and comorbidities found in our sample. The calculator predicted average mortality of 12% for emergency and 7% for nonemergency hip fracture surgery.…”
Section: Discussionmentioning
confidence: 65%
“…This mechanism may also be a contributing factor for the observation of lower mortality risk among low-to-moderate consumers because cardiovascular diseases are reported to be a frequent cause of death after hip arthroplasty [39]. …”
Section: Discussionmentioning
confidence: 99%
“…There is also a small mortality risk. 43,44 BACKGROUND TO THE RESTORE PROGRAMME NIHR Journals Library www.journalslibrary.nihr.ac.uk Attention has turned in recent years towards patient-reported outcomes in addition to technical outcomes. 45 Studies using patient-reported outcome measures (PROMs) suggest that mean pain and function scores after initial recovery from surgery are generally good.…”
Section: The Outcomes Of Hip and Knee Joint Replacementmentioning
confidence: 99%
“…43 Research in patients receiving a THR with comorbid cardiovascular disease has mainly focused on adverse events after surgery.…”
Section: Cardiovascular Diseasementioning
confidence: 99%